Role of FOXP3+ CD4+ and FOXP3+ CD8+ T Regulatory Cells in Obstructive Sleep Apnea. (23rd August 2013) - Anderson, Martin E.; Buchwald, Zachary; Sanford, Thomas R.; Aurora, Rajeev
Abstract : Objectives: 1) Examine the immune responses which may underlie adenotonsillar hypertrophy (ATH) associated with obstructive sleep apnea (OSA). 2) Discuss the role of effector and regulatory T‐cells in the inflammatory process within the tonsil and its association with apnea‐hypopnea index (AHI). Methods: Prospective tonsil specimens were collected from patients undergoing tonsillectomy for OSA at a tertiary‐care pediatric hospital between October 2012 and January 2013. Single cell suspensions of the tonsil samples were stained with fluor‐conjugated antibodies against CD3, CD4, CD8, FoxP3 (a regulatory T‐cell marker), and CD45RO (an activated effector T‐cell marker). The stained cells were then analyzed by flow cytometry. The levels of effector and regulatory T‐cells were then correlated with severity of disease, as quantified by AHI determined from polysomnography. Results: CD4 effector T‐cells (CD4 T‐eff) were significantly upregulated in pediatric patients with an AHI 5 relative to those with AHI < 5. This result, calculated by Mann‐Whitney two‐tailed test, indicates that the fraction of activated T‐cells increased with elevated AHI (P < 0.0095). FoxP3+ CD8 T‐cells (CD8 TcReg) were present at lower levels in patients with an elevated AHI. When these data were plotted as the ratio of CD8 T‐eff to CD8 TcReg versus AHI, a correlation coefficient of 0.67 was observed. Conclusions: The significant upregulation of CD4 T‐eff and the increased ratio of CD8 T‐eff to CD8 TcReg in relation to elevated AHI both suggest a immunologically‐driven response that is contributing to ATH and the development of OSA.